EFFECTS OF DEVELOPMENT PARTNERSHIP IN HIGHER EDUCATION PROJECT ON WELFARE STATUS OF RURAL WOMEN PROCESSORS IN OYO AND OSUN STATES, NIGERIA (2016)
Women are responsible for the bulk of agricultural processing activities in rural areas. Dearth of effective processing facilities has limited their productivity, thus predisposing them to low welfare status. Development Partnership in Higher Education (DELPHE) intervention sought to enhance women processors‟ capacity, however, its effect on their welfare status is yet to be ascertained. Therefore, the effects of DELPHE project on welfare status of rural women processors in Oyo and Osun states were investigated. A three-stage sampling procedure was used to select respondents for the study. Four and two Local Government Areas (LGAs) from Osun and Oyo states, respectively where DELPHE project was executed were purposively selected. Two participating and two non-participating communities were randomly selected from each of the LGAs. Ninety six (Oyo) and 120 (Osun) beneficiaries were proportionately selected from the participating communities. Using same structure for non-beneficiaries, registered processors from non-participating communities were selected to give 32 (Oyo) and 56 (Osun) respondents. Structured interview schedule was used to collect data on respondents‟ personal and enterprise characteristics, knowledge of processing activities, participation in DELPHE project activities, benefits derived, attitude of participants, constraints to processing activities and welfare status. Indices of participation (0-18: 0-8 low, 9-18 high), benefits derived (Low 0-6, high 7-14), attitude towards the project (Unfavourable 49-62, favourable 63-84 ) and welfare status ( Worse ₦750-₦5,836, better ₦5,837-₦16,500) were generated. Data were analysed using descriptive statistics, Pearson Product Moment Correlation, t-test, ANOVA and multiple regression at α0.05. Respondents‟ age and household size were 43.9±12.0 years and 6.0±2.0 person, respectively. Majority (87.0%) were married, while 52.7% of beneficiaries and 55.7% of non-beneficiaries had primary education. More beneficiaries (63.4%) had high level of participation in project UNIVERSITY OF IBADAN LIBRARY 3 activities, 65.7% highly benefitted from the project, while 56.7% had favourable attitude towards the project. Weighted mean of most important benefits derived were skill acquisition (0.84), enterprise expansion (0.78) and increase in yield (0.76). Most severe constraint to beneficiaries on their processing activities was lack of credit facilities (0.60), while high cost of processing equipment (1.54) was identified by non-beneficiaries. Welfare status of beneficiaries (₦7,629.53±1,710.60) was higher than that of non-beneficiaries (₦1,437.60±721.59). Welfare status of Osun state beneficiaries (₦8,719±0.33) was significantly higher than Oyo (₦1,281±0.33). More beneficiaries (67.3%) in the better welfare status derived higher benefits, while 41.9% in the worse welfare status had low benefit. Determinants of welfare status for Osun beneficiaries were years of processing (β= 0.189) and income (β=0.123), while for non-beneficiaries were occupation (β=-0.847) and household size (β=0.251). Determinants of welfare status among beneficiaries in Oyo were years of processing experience (β=0.373) and income (β=-0.267), while for non-beneficiaries were household size (β=0.123) and occupation (β= 0.847). The Development Partnership in Higher Education improved welfare status of beneficiaries from Oyo and Osun states. Income and years of processing experience were major determinants of beneficiaries‟ welfare status in both states. Keywords: DELPHE project, Beneficiaries‟ welfare status, rural women processors, rural communities Word count: 469